Bedside Matters: The Transformation of Canadian Nursing, 1900-1990 - Wishart, James M. (Labour / Le Travail, 1998)
The article reviews the book, "Bedside Matters: The Transformation of Canadian Nursing, 1900-1990," by Kathryn McPherson.